EICOSATETRAYNOIC ACID REGULATES PRO-FIBROTIC PATHWAYS IN AN INDUCED PLURIPOTENT STEM CELL DERIVED MACROPHAGE:HUMAN INTESTINAL ORGANOID MODEL OF ILEAL CROHN'S DISEASE. (26th January 2023) - Dreskin, Benjamin; Jurickova, Ingrid; Angerman, Elizabeth; Bonkowski, Erin; Denson, Lee
Abstract: INTRODUCTION: Biologics targeting TNF are the mainstay of therapy for children with Crohn's Disease (CD). However, a subset of patients do not respond, progressing to intestinal fibrosis requiring surgical resection. Prior studies have defined an ileal gene expression module linked to future strictures, and identified small molecules which may reverse this gene signature and suppress fibroblast activation. In the current study we developed a pre-clinical model system and tested a lead candidate, eicosatetraynoic acid (ETYA), a Peroxisome Proliferator-Activated Receptor (PPAR) agonist and arachidonic acid metabolism inhibitor. METHODS: Peripheral blood samples were collected from pediatric CD patients and induced pluripotent stem cell (iPSC) lines were generated. iPSC were differentiated into human intestinal organoids (HIOs) and macrophage-like cells. Macrophage:HIO co-cultures were exposed to lipopolysaccharide (LPS) with and without eicosatetraynoic acid (ETYA) pre-treatment. Flow cytometry and cytospin characterized macrophage activation markers and morphology. Co-culture populations were harvested, and RNA and conditioned media were isolated for downstream analysis. TaqMan Low Density Array, Luminex multiplex assay, immunohistologic staining, and sirius red polarized light microscopy were performed to quantify measures of inflammation and fibrosis, and to test whether introduction of ETYA abated any of these inflammatory or fibrotic changes. RESULTS: iPSC-derived macrophages exhibited morphology similar to primary macrophages, and expressed inflammatory macrophage cell surface markers including CD68 (Fig. 1A). LPS-stimulated iPSC-derived macrophages expressed a global pattern of gene expression by RNA sequencing enriched in CD ileal inflammatory macrophages (ToppCell Atlas, p=4.397E-117), and produced cytokines and chemokines implicated in refractory disease (Fig. 1B). Co-culture of LPS-primed macrophages with HIO led to up-regulation of the fibroblast activation genes ACTA2 and COL1A1 (Fig. 2). Under these conditions, HIO collagen content measured by sirius red staining and polarized light microscopy was increased (Fig. 2). ETYA pre-treatment prevented these pro-fibrotic effects of LPS-primed macrophages upon HIO gene expression and collagen content. However, LPS induction of macrophage IL1B, TNF, and OSM production was not suppressed by ETYA, suggesting an alternative mechanism of action upon HIO fibroblast activation and collagen content in the co-culture system. CONCLUSIONS: ETYA inhibits effects of LPS-primed macrophages upon HIO pro-fibrotic gene expression and collagen production. This was not associated with an effect of ETYA upon macrophage inflammatory cytokine production. Future studies will test alternate pathways including PPAR activation and arachidonic acid metabolism which may mediate this response.